Multibands of negative refractive indexes in the left-handed metamaterials with multiple dendritic structures - Zhu, Weiren; Zhao, Xiaopeng; Guo, Jiquan (Applied physics letters, 2008)
We demonstrate that the multibands of negative refraction indexes in the left-handed metamaterials may be appeared based on multiple dendritic structures cells. Employing microwave transmission experiment, the medium exhibits simultaneous negative refraction at the frequencies of 9.50, 10.24, and 10.78 GHz for the electromagnetic wave parallel incidence, and at the frequencies of 9.24, 9.98, and 10.78 GHz for normal incidence. The multiple dendritic metamaterials here open a way to prepare the cloak suitable for multifrequencies, especially for the cloak of infrared or visible frequency.